Implementasi Ekonomi Sirkular Melalui Platform Bisnis Digital - Hetifah Sjafudian; Nuzul Husnah; Siswanda H. Sumarto; Inta Budi Setya Nusa (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2026)
The global sustainability crisis caused by the linear economic model has resulted in 92.8% of material flows being wasted, while Indonesia faces a